Pengaruh Deblt To Equity Ratio, Price Earning Ratio, Earning Per Share Terhadap Harga Sahaml di Bursa Efek Indonesia - Fitri Melani; Indra Cahya Kusuma; Ayi jamlaludin Aziz (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This study aimls to test and determline the effect of Deblt To Equity Ratio (DER), Price Earning Ratio (PER), and Earning Per Share (EPS) on stock prices in blanking comlpanies listed on the Indonesia Stock Exchange for the period 2019-2023. The population of this study were all blanking comlpanies listed on the Indonesia Stock Exchange, The samlpling technique used Purposive Samlpling, so that out of 47 comlpanies that were samlpled, 10 comlpanies were selected. Data analysis used panel data analysis using the help of the Eviews.12 Student statistical tool. The results of the study showed that partially DER had a positive and significant effect on stock prices, while PER and EPS did not have a positive effect on stock prices, and simlultaneously DER, PER and EPS had an effect on stock prices.